Ficus deltoidea var. deltoidea (Mas Cotek): A Promising Natural Antioxidant Agent - Jani, Nor Akmalazura; Azman Shah, Nur Nabila; Preshahdin, Nur Atielia; Rokman, Farah Aina; Shamsuri, Nur Nazihah (2020)
Ficus deltoidea var. deltoidea or locally known as ‘Mas cotek’ is a medicinal plant which have been used traditionally to treat toothache, wound, rheumatism, sores as well as to improve blood circulation. This present study was conducted to determine phytochemicals and antioxidant activity of the n-hexane, ethyl acetate and methanol extracts of the leaves of F. deltoidea var. deltoidea. Total phenolic content (TPC) was determined according to the FolinCiocalteau colorimetric method, while the antioxidant activity was carried out using 2,2diphenyl-1-picryhydrazyl (DPPH) radical scavenging assay. Phytochemical screening on the n-hexane extract revealed that this extract consisted of terpenes and steroids, while the ethyl acetate extract contained phenolics, saponins, tannins, terpenes and steroids. Flavonoids, phenolics, tannins and glycosides were found to be present in the methanol extract. Among the three extracts, the methanol extract gave the highest total phenolic content (323.74 mg GAE/g extract) and also exhibited the strongest DPPH radical scavenging activity (IC 50 129.27 µg/mL). This study suggested that the leaves of F. deltoidea var. deltoidea might be useful as a promising natural antioxidant for pharmaceutical purpose.